The Effect Of Knowledge Sharing And Innovation Behavior On The Performance Of Batik Entrepreneurs - Nur Laily; Dyah Poespita Ernawati (Jurnal Manajemen, 2020)
The purpose of this research was to determine the effect of knowledge sharing and innovation behavior on the performance of Batik entrepreneurs. It was also meant to examine the indirect impact of knowledge sharing on entrepreneurial performance through innovation behavior as a mediator. This is a causality study with 62 batik SME in Surabaya as samples. The inclusion criteria involved batik businesses with a minimum of 3 employees, the enterprise owned by Indonesian citizens, a legal entity, and at least 3 years operation. This research uses primary data with questionnaire and interviews with batik entrepreneurs as data collection instruments. The Partial Least Square (PLS) and Sobel tests to determine the indirect effect of variables. The results showed that knowledge sharing affected the performance of Batik entrepreneurs and their innovation behavior. The Sobel test results showed that innovation behavior mediates the influence of knowledge sharing and entrepreneurial performance.